New venture and business development in tertiary environment. - Goh, Ching Sie. (2008)
This report is the culmination of a year long project where we have to generate new business ideas and select the best one to write a feasible business plan. During the course of our project, we have conducted literature review of numerous websites to research on whether our project idea is innovative. Upon confirmation that our business idea is creative, we commenced on identifying the needs and wants of various customers segments as well as their customer profile. We have also identified the key success factors that a company must possess to be successful in our selected industry.